2D MXene Materials for Sodium Ion Batteries: A review on Energy Storage. (May 2021) - Aslam, Muhammad Kashif; AlGarni, Tahani Saad; Javed, Muhammad Sufyan; Shah, Syed Shoaib Ahmad; Hussain, Shahid; Xu, Maowen
Highlights: This review primarily emphasis the synthesis, structure and energy storage applications. MXenes having expanded interlayer distance, properly functionalized surface and heterolayer structure (composites) could exhibit excellent electrochemical performance. Presents a personal outlook for the further development of MXene in the field sodium-ion batteries (SIBs). Abstract: The performance of electrochemical energy storage (EES) devices highly rely on the in-built properties of the material. Due to the excellent properties of 2D materials, a much of research has been conducted on 2D materials. In the past decade, a novel family of 2D carbides and nitrides materials have been successfully prepared called MXene using stripping method, from layered precursors. The accessibility of solid solutions, the control of surface terminals and the latest innovation of MXene layers provide potential for the preparation of several new structures. Multifunctional chemistry of MXene allows adjustments to the performance in the field of energy storage. In addition, some distinctive EES properties have been revealed. With the advancement in EES field, it is necessary to understand the application of MXene in the EES field in time. This review primarily emphasis the synthesis, structure and energy storage application of MXene are introduced. More importantly, the theoretical and experimental electrochemical performances are compared and criticized. Finally, the future research scope and outlook of MXene in the field of energy storage systems is prospected. Graphical abstract: Image, graphical abstract